A macroscopic classification of the embryonic development of the one-sided livebearer Jenynsia multidentata (Teleostei: Anablepidae) - López-Rodríguez,Nathalia C. (2017)
ABSTRACT This study proposes eight stages according to the main discernible changes recorded throughout the embryonic development of Jenynsia multidentata. The development of morphological embryo structures, pigmentation, and changes in tissues connecting mother and embryo were included in the stage characterization. From the fertilized egg (Stage 1), an embryo reaches the intermediary stages when presenting yolk syncytial layer (Stage 2), initial pigmentation of the outer layers of the retina and dorsal region of the head (Stage 3), and the sprouting of the caudal (Stage 4), dorsal and anal fins (Stage 5). During the later stages, the ovarian folds enter the gills, and the body pigmentation becomes more intense (Stage 6), the body becomes elongated (Stage 7), and there is a greater intensity in body pigmentation and increased muscle mass (Stage 8). The dry weight of the batches varied between 0.6 ± 0.3 mg (Stage 3) to 54.6 ± 19.7 mg (Stage 8), but the dry weight of the maternal-embryonic connecting tissues remained almost constant. After controlling the effect of those reproductive tissues, the gain in dry weight of the batches throughout development increased exponentially from Stage 6, reflecting the increase in size and weight of the embryos due to matrotrophy.